(untitled) (Indonesian Journal of Civil Engineering Study, 2026)
Transportation forms the foundation of economic development. Advances in transportation are crucial for supporting economic activities and accelerating both regional and national development. As economic activity increases, the demand for mobility also rises. To meet this growing demand, the number of motorcycles in Indonesia has increased by 5.95%. This growth has contributed to traffic congestion, particularly at intersections, which are convergence points for various traffic flows. According to data from Statistics Indonesia (BPS), Central Java Province ranks third in terms of the highest number of motorized vehicles, with Demak Regency being one of the areas most affected. One intersection in Demak Regency that frequently experiences traffic congestion is the intersection of Jalan Raya Mranggen and Jalan Raya Kauman. This condition disrupts community mobility and increases the risk of traffic accidents. Therefore, the purpose of this study is to analyze the intersection capacity, degree of saturation, and level of service in order to optimize traffic flow performance. The traffic performance at the intersection of Jalan Raya Mranggen and Jalan Raya Kauman can be evaluated by analyzing the level of service (LOS) at the intersection. This evaluation refers to the Indonesian Highway Capacity Guidelines (PKJI) 2023, which provides results in the form of intersection capacity, degree of saturation, delay, and level of service. The method used in this research involves direct observation and data collection at the study site. Based on the evaluation results, the intersection of Jalan Raya Mranggen and Jalan Raya Kauman has a capacity (C) of 2,952 PCU/hour, with a total traffic volume of 3,637 PCU/hour, resulting in a degree of saturation of 1.23 and a delay value of 50.57 seconds/PCU. The conclusion drawn from this study is that the level of service (LOS), as indicated by the delay value of 50.57 seconds/PCU, falls under level E. This signifies a poor level of service at the intersection, indicating the need for intersection management in the form of transitioning from an unsignalized to a signalized intersection.